Underground excavations in rock - Hoek, Evert (The Institution of Mining and Metallurgy, 1980)
Planning considerations - Classification of rock masses - Geological data collection - Graphical presentation of geological data - Stresses around underground excavations - Strength of rock and rock masses - Underground excavation failure mechanisms - Underground excavation support design - Rockbolts, shotcrete and mesh - Blasting in underground excavations - Instrumentation - Appendix.